EFEKTIVITAS PENGGUNAAN APLIKASI POLRI SUPER APP DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK YANG TERINTEGRASI DI POLDA LAMPUNG - Azizah, Azizah; Farida, Ida (Triwikrama: Jurnal Ilmu Sosial, 2024)
This Polri Super (App) is an application specifically designed by the National Police for the public to make it faster and easier to carry out excellent service from the existing police just by using a smartphone. Through this application, the public can access services such as processing driving licenses, vehicle registration, making online SKCK, information relate to E-Tickets, information on vulnerable areas and DUMAS (public complaints). The research method used in this research is descriptive-qualitative. The obstacles to the Polri Super (App) are that the server is sometimes not smooth, and there are account verification obstacles that are too complicated, so people are reluctant to use the application, which is a problem for users under Gen Z. The aim of this research is to determine the effectiveness of using the Polri Super (App) in improving the quality of integrated public services in thE Polda Lampung. To find out the supporting and inhibiting aspects of using the Polri Super (App) in improving the quality of integrated public services in the Polda Lampung. The results of this research showed that the service on the Polri Super (App) was not yet effective because there were still problems with the network.